Neuron-derived mitochondrial DNA (mtDNA) activates microglia via the Z-DNA binding protein 1 (ZBP1)-mediated pathway in mild traumatic brain injury - Michela Marcatti; Javier Allende Labastida; Tony Zifeng Tang; Akbar Ahmad; Christina Payne; Nora Schwartz; Paula Villarreal; Olivia D. Solomon; Gracie Vargas; Ping Wu; Bartosz Szczesny (Proceedings of the National Academy of Sciences, 2026)
Traumatic brain injury (TBI) is a leading cause of morbidity and mortality, with closed-head mild TBI (mTBI) accounting for nearly 90% of all cases. Early pathological events include microglial activation and neuronal mitochondrial dysfunction; however, their interconnection in mTBI remains poorly understood. Using a clinically relevant closed-head weight-drop mouse model, we identified mitochondrial DNA (mtDNA)-specific damage and increased expression of innate inflammatory markers (IL-1α/β, IL-6, TNFα, and CXCL1) in the cerebral cortex during the acute mTBI phase. Mechanistically, neurons subjected to in vitro injury model of mTBI exhibited early mtDNA-specific damage followed by mtDNA release via extracellular vesicles (EVs) together with the neuronal and exosomal markers. The released neuronal mtDNA induced a robust microglial activation mediated by binding to the cytoplasmic DNA/RNA sensor Z-DNA–binding protein 1 (ZBP1), triggering activation of the ZBP1–TBK1–IRF3 pathway resulted IL-6 and TNFα expression. An early, enhanced amounts of mtDNA, neuronal and exosomal markers were measured in EVs circulating in the blood of mice subjected to mTBI. ZBP1 knockout (KO) mice displayed suppressed microglial—but not astrocytic—activation in the cortex during the acute mTBI phase. We also measured accumulation of mtDNA-specific damage in the hippocampus during the postacute mTBI phase. The absence of microglial activation in ZBP1 KO mice exacerbated hippocampal-related memory deficits in the postacute mTBI phase. Collectively, our findings identify mtDNA–ZBP1 signaling as a key mechanism regulating microglial activation in mTBI.